Evaluation of the limitations and methods to improve rapid phage-based detection of viable Mycobacterium avium subsp. paratuberculosis in the blood of experimentally infected cattle - Swift, Benjamin M.C.; Huxley, J.N.; Plain, Karen M.; Begg, Douglas J.; de Silva, Kumidika; Purdie, Auriol C.; Whittington, Richard J.; Rees, Catherine (BioMed Central, 2016)
Background